A Study of Aesthetic and Functional Outcome Following Structural Fat Grafting for Facial Scars and Contour Deformity. Issue 4 (December 2020) - Rao, Anantheswar Y. N.; Reddy, Sudarshan Nagireddy; Chandrappa, Ashok Basroor; Vasudevan, Srikanth; Batth, Rittu
Study Design: This is a prospective observational study of 60 consecutive cases with facial scars and contour deformity who underwent structural fat grafting. Objectives: The aim of the present article is to highlight how fat grafting helps to improve aesthetic and functional outcome in facial scars and contour deformities. It also highlights the factors that need to be considered while planning autologous fat grafting to get better aesthetic results. Methods: This is a prospective observational study of 60 consecutive cases with facial scars and contour deformity. The study was conducted from May 2014 to April 2019 in a tertiary care hospital. All the patients were followed up for a minimum period of 1 year from the date of surgery. Assessment of post-operative aesthetic outcome, in terms of satisfaction, was done using the Visual Analogue Scale (VAS), which ranges from 1 to 10 by the patient and operative surgeon. Results: The mean age was 30.8 9.8 years. Out of 60 patients, 20 patients underwent additional procedure like dermabrasion and collagen dressing to improve aesthetic outcome. Among 60 patients, 24 patients had transient edema and 10 patients had bruising at the recipient site. There were no major donor site complications except pain which was managed conservatively. Mean patient satisfaction score is 7 and mean surgeon satisfaction score is 7.25. Conclusion: Despite the ongoing concerns about survival and longevity of fat grafts and also unpredictability of long-term outcomes, fat grafting has become a very useful surgical tool to improve the quality of facial scars and correct contour deformity. Our series shows excellent outcome both clinically as well as from the patient satisfaction. Future research is warranted in the fields of the adipocyte derived stem cells and to expand the clinical application of fat grafting.